PENGARUH IKLIM KOMUNIKASI DENGAN KINERJA PEGAWAI DI KANTOR KEMENTERIAN AGAMA KOTA BANJARMASIN - Muhammad Agus Humaidi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
This study aims to determine the communication climate and employee performance in the Office of the Ministry of Religious Affairs of Banjarmasin, in addition to know the influence between the communication climate with the performance of employees in the Office of the Ministry of Religious Affairs Banjarmasin. The method used is a quantitative research approach and a research instrument with a questionnaire that is analyzed with Chi Square Goodness Of Fit and Simple Linear Regression.The results showed that the communication climate of employees in the Office of the Ministry of Religious Affairs of Banjarmasin is quite good. While the performance of employees in the Office of the Ministry of Religious Affairs of Banjarmasin including less good category. In addition there is no influence between the communication climate on the performance of employees in the Office of the Ministry of Religious City of Banjarmasin.